ETIKA BERMEDIA SOSIAL BERDASARKAN UNDAN-UNDANGAN DI INDONESIA - Penuam, Acow Hendry Gunawan; Mailani, Metriana; Taopan, Eby; Neonbeni, Rosalia; Nenotek, Asrin Deweli; Mas'ud, Fadil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of social media in Indonesia provides a very broad space for freedom of expression for the public. However, this freedom is often misused due to a lack of understanding of ethics and law, triggering various social problems such as hate speech, cyberbullying, and the unauthorized spread of confidential data. This study aims to examine and formulate the boundaries of social media ethics based on legal rules currently applicable in Indonesia. The method used is qualitative with a literature study approach. Secondary data was collected from various recent academic literature and official state documents, then analyzed using content analysis techniques. The results show that cyberspace is not a room immune to the law. All forms of public digital interaction have been strictly bound by the Electronic Information and Transactions Law and the Personal Data Protection Law. Any form of violation that harms the dignity and privacy of others can be subject to very severe criminal sanctions. Nevertheless, law enforcement by the police is considered insufficient and must be balanced with the role of civic education to build the superior character of the community from an early age. The conclusion of this study confirms that being polite in cyberspace is a legal obligation. Strong cooperation between compliance with the law and the moral responsibility of all internet users is urgently needed to realize a smart, safe, and civilized digital public space.